Intracranial Teratoma in Young Adult Female: Case Report - Marques, Nathan Kulkys; Haag, Karine; Buffara, Leonardo Trindade; Steclan, Chelin Auswaldt; Della, André Possamai; Nones, Diogo Pasquali; Junior, Oscar Nelson Reimann; Peres, Gabriel Hoher; Oliveira, Arlindo Américo de; Júnior, Amaurí Batista de Oliveira; Brito, Leonard Rocha Fonseca de; Lang, Michael Ricardo; Cabral, Filipe Laurindo (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2022)
Intracranial teratoma corresponds to a type of germ cell tumor (GCT) of the central nervous system which is characterized by the presence of tissues derived from the germinal layers, which may have hair and adipose tissue inside, for example. The literature on the subject is scarce, and the T2 magnetic resonance imaging (MRI) pattern commonly found is that of a heterogeneously hyperintense mass and, after contrast, teratoma presents heterogeneous enhancement. Therefore, the present case report aims to present atypical results of a GCT in a young adult woman. Data analysis and compilation were performed from medical records, as well as the neuroimaging study. Thus, the present case report demonstrates neuroimaging findings with homogeneous postcontrast enhancement in an adult patient, with an unusual age profile when compared with most of the studies published so far. This demonstrates that it is possible to have atypical neuroimaging findings for mature teratomas and that they can behave in a less aggressive way, not requiring adjuvant postoperative therapies.
Keywords: germ cell tumor; intracranial germ cell tumor; mature teratoma